Refugees, Mobilization, and Humanitarian Aid: Evidence from the Syrian Refugee Crisis in Lebanon. (May 2020) - Masterson, Daniel; Lehmann, M. Christian
This article examines whether refugees are prime candidates for recruitment into armed groups and whether humanitarian aid to refugees impacts their choice to join armed groups. First, our original survey data of 1, 358 Syrian households in Lebanon provide evidence that mobilization among the refugee population is low at baseline—the first empirical estimates of the magnitude of the rate of Syrian refugees returning home to fight. Second, leveraging as-if random assignment around a strict altitude cutoff for a United Nations cash transfer program for Syrian refugees, we find little evidence that the aid program had a large effect on mobilization. If anything, our estimates indicate a small decrease in mobilization. Our results stand in contrast to published literature arguing that refugees are prime candidates to join armed groups and humanitarian aid to refugees may support armed groups and fuel recruitment.